Penggunaan strategi pembelajaran trading place untuk meningkatkan aktivitas belajar ilmu pengetahuan sosial siswa sekolah dasar - Marwanti, Endah; Yogotomo, Dwi; Ambawani, Rohmah Fitri (Indonesian Journal of Learning and Educational Studies, 2025)
The purpose of this research is to find out whether the use of trading place learning strategies can increase social studies learning activities in class IV SD Negeri 2 Glodogan, Klaten. The research method used is the spiral model which consists of 4 components, namely planning, implementation, observation, and reflection. The results showed that through cycle I and cycle II there was an increase in student learning activities. The improvement in this study can be seen from the results of the data obtained from cycle I to cycle II. This can be explained from the beginning in the pre-cycle after working on evaluation questions and the results of observing learning activities to obtain the final result of an average percentage of 62.1% in the good category and 40% in the bad student category. Then in cycle I after working on evaluation questions and observations of student learning activities the final results obtained an average percentage of 74.1% in the good category and 48.1% in the bad category. Judging from the results obtained in cycle I, the expected intervention had not yet been achieved, so the researcher continued to cycle II. after cycle II has been completed the results of working on evaluation questions and the results of observing student learning activities obtain the final results of an average percentage of 85.9% and 77.5% in the good category.